2015
DOI: 10.1093/jac/dkv164
|View full text |Cite
|
Sign up to set email alerts
|

Not in my backyard: a systematic review of clinicians' knowledge and beliefs about antibiotic resistance

Abstract: Clinicians believe antibiotic resistance is a serious problem, but think it is caused by others. This needs to be accommodated in interventions to reduce antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 29 publications
6
90
0
2
Order By: Relevance
“…A review of the human literature revealed a widespread awareness by physicians of the issue of antimicrobial resistance in human medicine. 42 However, in parallel with findings in this study, this concern was often accompanied by a belief that the responsibility for the generation of such resistance lies with other professionals and in other medical establishments. 19,43 …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A review of the human literature revealed a widespread awareness by physicians of the issue of antimicrobial resistance in human medicine. 42 However, in parallel with findings in this study, this concern was often accompanied by a belief that the responsibility for the generation of such resistance lies with other professionals and in other medical establishments. 19,43 …”
Section: Discussionsupporting
confidence: 73%
“…45,46 The predominant opinion amongst participants was that this was a sporadic event and that any threat was minimal. Whilst opinions from human prescribers have implicated the overuse of antimicrobials in livestock in human resistance profiles, 42 it seems veterinary opinion is divided. 16,17,47 However, there was a shared opinion amongst the study population that antimicrobial resistance in human medicine was mainly driven by use in humans, an opinion echoed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…10 They also noted that social cognitive theory also explains why clinicians experience a conflict between minimising AMR and avoiding clinical deterioration in their patients when prescribing antibiotics: AMR is a distant and physically removed consequence of antibiotic prescribing, whereas patient distress and clinical deterioration are proximal and confronting consequences. Two-thirds of our GPs viewed patients as still being too demanding of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…However, the view of 'not in my backyard' , [3] which suggests that others overprescribe antibiotics and drive resistance, may contribute to inappropriate prescribing behaviours. [4,5] The underlying cognitive bias for the students' contradictory views need to be explored and may represent yet another enabler to affect behaviour.…”
Section: Guest Editorialmentioning
confidence: 99%